Venous Thromboembolism in Children with Cancer and Blood Disorders - Ko, Richard H.; Thornburg, Courtney D. (Frontiers in Pediatrics, 2017)
Venous thromboembolism (VTE) in children is multi-factorial and most often related to a combination of inherited and acquired thrombophilias. Children with cancer and blood disorders are often at risk for VTE due to disease related factors such as inflammation and abnormal blood flow and treatment related factors such as central venous catheters and surgery. We will review risk factors for VTE in children with leukemia, lymphoma and solid tumors. We will also review risk factors for VTE in children with blood disorders with specific focus on sickle cell anemia and hemophilia. We will present the available evidence and clinical guidelines for prevention and treatment of VTE in these populations.